The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00264-010-0994-8
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic field therapy results in healing of full thickness articular cartilage defect

Abstract: This study aimed to determine the efficacy of PEMF (pulsed electromagnetic field) treatment in experimental osteochondral defect healing in a rabbit model. The study was conducted on 12 New Zealand white rabbits. Six rabbits formed the study group and six rabbits the control group. The right knee joints of all 12 animals were exposed and a 3.5-mm diameter osteochondral defect was created in the trochlear groove. The defect was filled with calcium phosphate scaffold. Six animals from the study group were given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Alternative approaches to improve regeneration capacity in explants treated with PEMFs may include: 1) increasing exposure amplitude; 2) increasing exposure duration; 3) increasing number of exposures to a value greater than 1; 4) exposing MSC-seeded explants directly to PEMFs or; 5) a combination of the above. In fact, Esposito et al have previously reported induction of chondrogenic differentiation upon PEMF treatment [14] and several in vivo studies have demonstrated beneficial effects of this therapy on clinical symptoms of animals and humans with osteoarthritis [11,12]. It has to be mentioned though that these studies applied 6 weeks of daily treatment of the injured joint, whereas our study employed single 10 minute prestimulation of chondrogenically induced MSCs and unstimulated ex vivo cartilage explants.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Alternative approaches to improve regeneration capacity in explants treated with PEMFs may include: 1) increasing exposure amplitude; 2) increasing exposure duration; 3) increasing number of exposures to a value greater than 1; 4) exposing MSC-seeded explants directly to PEMFs or; 5) a combination of the above. In fact, Esposito et al have previously reported induction of chondrogenic differentiation upon PEMF treatment [14] and several in vivo studies have demonstrated beneficial effects of this therapy on clinical symptoms of animals and humans with osteoarthritis [11,12]. It has to be mentioned though that these studies applied 6 weeks of daily treatment of the injured joint, whereas our study employed single 10 minute prestimulation of chondrogenically induced MSCs and unstimulated ex vivo cartilage explants.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, it has been shown that pulsed electromagnetic field (PEMF) treatment of injured rabbit knees can significantly improve histological scores and hyaline cartilage formation after 6 weeks of daily PEMF treatment for one hour a day [11]. In 28 elderly humans with bilateral knee osteoarthritis, PEMF stimulation at 3 times per week over 6 weeks significantly improved pain, stiffness, and physical function in comparison to the untreated contralateral joint [12].…”
Section: Introductionmentioning
confidence: 99%
“…During subchondral drilling, bone marrow cells migrate and endogenous growth factors are released from subchondral bone [Khan et al, 2010]. These endogenous growth factors may be able to initiate differentiation of bone marrow cells and cause osteochondral defects to profit from EMF stimulation [Boopalan et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, there are scarce reports, if any, on scaphoid fractures (4,5). The objective of this case report is to show delayed union fracture as a common complication of scaphoid fracture and to postulate PEMF as an effective treatment option for such a condition, reflected by our clinical and radiological evaluations and supported by a thorough review of the literature.…”
Section: Introductionmentioning
confidence: 88%